Hubungan Lama Masa Studi terhadap Tingkat Pengetahuan tentang Gejala, Diagnosa, Tatalaksana Covid-19 Pada Mahasiswa Kedokteran Universitas Sumatera Utara: cross-sectional study - Intania Cahya Sari Bangun (Faculty of Medicine, Universitas Andalas, 2021)
AbstractPurpose: The study aimed to identify the different level of knowledge in medical students of Universitas Sumatera Utara based on the length of study. Methods: We conducted a questionnaire-based survey at Universitas Sumatera Utara, Medan, Indonesia. The participants were from the 2-4 grades of medical school, 91 participants in total. This study started from March 2020 to December 2020. The questionnaire designed to identify the different level of knowledge of the students. Then, we analyzed the correlation using Kolmogorov-Smirnov test.Results: From 91 respondents, 21 (23,1%) have a good knowledge, 40 (44%) have enough knowledge, and 30 (33%) doesn’t have enough knowledge about Covid-19. Most respondents are 20 years old (29,7%), female (29,7%), live in Medan (69,2%), and most of the respondents were bataknese (40,7%). There is a correlation between the length of study and the level of knowledge about Covid-19 on medical students of Universitas Sumatera Utara (p= 0,033).Conclusion: This study shows that there is a correlation between the length of study and the knowledge about Covid-19 on medical students of Universitas Sumatera Utara.